Wound healing activity of topical Phaleria macrocarpa extract in type 2 diabetic rats - Sulistyoningrum, Evy; Rosmelia, Rosmelia; Fidianingsih, Ika; Narantika, Shindy Galuh; Cleopatra, Neysa Nurprahutri; Azzahra, Fathimah (Universa Medicina, 2024)
BackgroundHyperglycemia interrupts wound healing, causing persistent and non-healing wounds. Phaleria macrocarpa extract (PME) has anti-diabetic, anti-inflammatory, antimicrobial, and antioxidant properties. This study aimed to assess P. macrocarpa activity on skin wound healing in diabetic rats. MethodsAn experimental study performed on 25 male Wistar rats. Ointments were prepared by adding vehicle (w/w) to PME at the desired concentration. Diabetes was induced by injecting rats with nicotinamide (NAD) 230 mg/kg and streptozotocin (STZ) 65 mg/kg. After hyperglycemia was confirmed, animals were randomly grouped into: i) normal rats, ii) diabetic rats; iii) diabetic rats + 2.5% ointment; iv) diabetic rats +5% ointment; and v) diabetic rats +10% ointment. Full-thickness skin wounds were induced on the dorsum and treatment was applied daily for 3 and 7 days, respectively. On days 4 and 8, wound closure was measured and animals were sacrificed for tissue samples. Wound healing was evaluated by measuring malondialdehyde (MDA) in tissue homogenates of the dermal wounds and analyzing histological changes by hematoxylin-eosin and Sirius-red staining. ResultsPME 10% ointment improved MDA levels and wound closure of inflammatory and proliferation phases. In inflammatory phase, 5% and 10% ointment reduced inflammation severity compared with diabetic rat group (p<0.05). In proliferation phase, PME 10% ointment group had a higher wound histological score (characterized by epidermal regeneration, fibroblast count, granulation tissue, and angiogenesis), and higher collagen bundle density compared with untreated groups (p<0.05).  ConclusionsTopical P. macrocarpa improves inflammatory and proliferation phases of excision wound healing in type 2 diabetes.